Parasitic zoonoses : report of a WHO expert committee, with the participation of FAO, meeting held in Geneva from 14 to 20 November 1978 - WHO Expert Committee on Parasitic Zoonoses; World Health Organization (Geneva : World Health Organization, 1979)
Deals with the protozoa, helminths and arthropods transmissible between man and lower animals, emphasizing methods of surveillance, prevention, and control that can reduce the incidence of zoonoses and foodborne disease. Parasitic conditions covered include toxoplasmosis, sarcosporidiosis, leishmaniasis, African and American trypanosomiases, malaria, Pneumocystis carinni infection, babesiosis, amebiasis, giardiasis and balantidiasis. The opening section concentrates on the significant economic losses caused by these infections, particularly in draught animals, meat, milk, and other foods and products of animal origin. Factors identified as influencing prevalence include the introduction of large-scale intensive animal production and social and cultural customs that determine food habits and attitudes towards domestic animals. The most extensive section concentrates on the principles of surveillance, prevention, control, and elimination of parasitic zoonoses. A system for classification of zoonoses is also presented. Other sections cover immunological tests used for a variety of zoonoses and list diseases in man, the causative organism, and the main vertebrate animals involved. The report concludes with recommendations for field and laboratory workers, parasitologists, and veterinary and public health agencies
Introduction -- Socioeconomic aspects -- Factors influencing prevalence -- Principles of surveillance, prevention, control, and elimination -- Protozoan infections -- Cestode infections -- trematode infections -- Nematode infections -- Infections caused by pentastomids and arthropods -- Other parasitic and allergenic arthropods -- References -- Acknowledgements -- Annexes.
Keywords: Zoonoses; Parasitic Diseases